The reaction of self-fertile alfalfa lines to inoculation with nodule bacteria - Pukhtaievych, P.; Kukol, K.; Vorobey, N.; Kots, S. (The Journal of V.N.Karazin Kharkiv National University. Series «Biology», 2020)
Under the conditions of a model pot experiments, the reaction of the self-fertile lines of alfalfa Kishvardy 46, Kishvardy 27, Vertus and Ziguen to inoculation with nodule bacteria Sinorhizobium meliloti AC48 and AC88 was studied. As a result of studies, it was found that the intensity of assimilation of N2 by symbiotic systems created with the participation of various genotypes of alfalfa and active strains of S. meliloti is one of the main factors that affects the vegetative mass yield of this important forage crop. Self-fertile lines of Medicago sativa L. plants, inoculated with different strains of rhizobia were characterized by higher rates of the mass formed on the root nodules, compared to the control plants of the alfalfa variety Yaroslavna. The traditional dynamics of nitrogen-fixation activity of root nodules was maintained in all the symbiotic systems studied by us, with low values in the stems formation stage and intensive growth in the budding and flowering stages. The highest level of nitrogen fixation and vegetative growth of plants (values of plants green and dry mass, roots and root nodules mass) was established by inoculation of alfalfa line Kishvardy 46 with strain S. meliloti AC48. During the growing season the indices of the mass of nodules formed on the roots of these plants were higher by 1.8–2.3 times, the green mass by 1.2–1.6 times and the height of the plants 1.2–1.4 times as compared to the control. In the flowering stages the nitrogen-fixation activity of the symbiotic complex of plants of the Kishvardy line 27 and nodule bacteria S. meliloti AC48 exceeded the values in the symbiotic systems formed with the participation of the same strain and plants of the Ziguen and Vertus lines by 13.0 and 39.4 %. The lowest values of nitrogen fixation activity were observed by inoculation of plants of the Vertus and Ziguen lines with active strains S. meliloti AC48 and AC88 compared to the symbioses formed by the plants of the Kishvardy lines 27 and 46, as well as of the control-variety Yaroslavna with the noted strains. A stimulating effect of inoculation of alfalfa seeds of different genotypes on the growth and development of plants was noted, as evidenced by the positive dynamics of the increase in above-ground mass, the accumulation of dry matter and higher than the control values (indicators) of plant height during the growing season.